Reading strategy instruction in L2 (English): an investigation into effects of L2 on L1 (Persian) - Talebi, Seyed Hassan; Serahati, Abdolreza (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study intended to find out which language (English as L2 or Persian as L1) would benefit more as a result of reading strategy instruction in L2. Forty students were given tests of reading comprehension and reading strategy questionnaires both in L2 and L1 as pretest and posttest. The control group was taught in the traditional way through teaching of vocabulary and grammar, but the experimental group received these along with reading strategy instruction (RSI). Results indicated the experimental group outperformed the control group on reading strategy questionnaire and reading performance in L2 and L1. Moreover, differences in improvements from pretest to posttest of reading strategies were not significant between L2 and L1, though this was significant for the reading test as the participants gained more in L2 than in L1. Although reading strategies transfer cross linguistically, it seems the language in which RSI is given benefits more in reading performance. Through teaching reading strategies in L2, awareness and use of reading strategies as well as reading ability of EFL students can be improved both in L2 and L1.